Diagnostic and Therapeutic Challenges of a Large Pleural Inflammatory Myofibroblastic Tumor - Judith Loeffler-Ragg; Johannes Bodner; Martin Freund; Michael Steurer; Christian Uprimny; Bettina Zelger; Christian M. Kähler (Case Reports in Pulmonology)
We report a 48-year-old woman with a pleural pseudoneoplasm requiring different diagnostic and therapeutic strategies. After initial presentation with increasing dyspnoea, temperature, dry cough, and interscapular pain diagnostic processing showed a large mediastinal mass with marked pleural effusion and high metabolic activity in the 18F-FDG-PET/CT. Extensive CT-guided biopsy of the tumor reaching from the visceral pleura into the right upper lobe revealed no malignancy, but a marked inflammatory tissue reaction containing foam cells. Initial empiric antibiotic therapy was temporarily successful. However, in the further course the mass relapsed and was resistant to antibiotics and a corticosteroid trial. With the working hypothesis of an inflammatory myofibroblastic tumor the patient underwent surgical tumor resection, finally confirming the suspected diagnosis. Due to residual disease intravenous immunoglobulins were administered leading to sustained response. This case with a pleural localisation of a large inflammatory pseudotumor with responsiveness to immunomodulation after incomplete resection extends the reported spectrum of thoracopulmonary manifestations of this rare entity.